Association between Maternal FUT2 204A>G (rs492602) Genetic Polymorphism and Congenital Heart Disease in the Indian Population: A Study in Maternal-fetal Dyads - Tella, Sunitha; Chukkayapalli, Sowmya Gayatri; Akka, Jyothy; Uppala, Satyanarayana (Cell and BioPharmaceutical Institute, 2023)
Background: FUT2 secretor genetic variants are strongly associated with absorption and circulatory levels of vitamin B12, thereby affecting folate metabolism pathway. The aim of this study was to evaluate the association between maternal FUT2 204A>G (rs492602) genetic polymorphism and CHD in the Indian population.Materials and method: One hundred and ten pregnant women who were vitamin B12 deficient with fetuses diagnosed with CHD were included in the case group and an equal number of healthy pregnant women with normal fetuses were selected as the control group. DNA was extracted from blood and umbilical cord tissue samples, and genotyped for FUT2 rs492602 polymorphism using allele-specific polymerase chain reaction. Hardy–Weinberg equilibrium test was used to calculate allele and genotype frequencies.Results: Significant increase in the frequency of AG (odds ratio=2.25; 95% CI: 1.25–4.05; p=0.009) and GG (odds ratio=3.51; 95% CI: 1.47-8.43; p=0.006) genotypes as well as G allele of FUT2 rs492602 were observed in the maternal case group. Furthermore, in the fetus case group, there was a significantly higher incidence of GG genotype (odds ratio=2.87; 95% CI: 1.26–6.57; p=0.018) and G allele (odds ratio=1.70; 95% CI: 1.15–2.53; p=0.009).Conclusion: FUT2 rs492602 are associated with CHD in the Indian population. Maternal genetic polymorphism that regulates vitamin B12 metabolic pathway might influence fetal cardiac development, thus serving as a predictor for CHD.Keywords: congenital heart disease, FUT2, single nucleotide polymorphism (SNP), vitamin B12